PHYSICAL-CHEMICAL STUDY OF ZnO-MWCNT NANOPARTICLES FOR A WATER FLOODING EXPERIMENT IN ENHANCED OIL RECOVERY (EOR) - ALNARABIJI, MOHAMAD (2014)
Extracting the trapped oil is still one of the main challenges faced by the oil and gas industry to this point of time. Conventional recovery methods like chemical, thermal, alkaline and gas are found not able to meet the expectations and demands of the current era. Therefore the industry has started to look forward at non-conventional methods. Nanotechnologywith the impressive size ofparticles gave the hope to tackle this problem. Therefore, injection ofdielectric nanofluids with different surface nature accompanied with electromagnetic waves has been proposed to enhance recovery efficiency in enhanced oil recovery(EOR) stage. It was found that the viscosity of the dielectric nanofluid changes and increases with exposure to electric field which can provide better sweep efficiency during water flooding experiment. Hydrophilic Zinc oxide (ZnO) and hydrophobic MultiWall Carbon Nanotubes (MWCNT) were used as dielectric material. Successfully, ZnO was synthesized by sol-gel method in the presence of gelatin type B as a gelatinization agent with mean size 20 nm. Then the microstructure properties of both of ZnO and MWCNT were investigated.